1985
DOI: 10.1111/j.1365-2311.1985.tb00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen‐feeding and the host specificity and fecundity of flower thrips (Thysanoptera)

Abstract: 1. Flower thrips could feed on pollen of a wide range of sizes and were unaffected by exine spines. One species of thrips was unable to feed on very adhesive grains.2. The proportion of time spent feeding on each species of pollen (in seconds per minute of exposure) reflected the known host specificities. Host-specific thrips could distinguish their host pollen, apparently without probing. 3.Kukothrips pisivorw (Westwood) appeared to have a higher rate of ingestion of a host pollen than of four non-host pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 33 publications
1
82
0
Order By: Relevance
“…The function of the gut bacteria for their host has not yet been studied and we test their impact on food conversion in the thrips. Thrips feed primarily on leaf parenchyma, leaf petals and pollen of a large number of species (Kirk 1985;Yudin et al 1986). …”
Section: Materials and Methods (A) The Model Systemmentioning
confidence: 99%
“…The function of the gut bacteria for their host has not yet been studied and we test their impact on food conversion in the thrips. Thrips feed primarily on leaf parenchyma, leaf petals and pollen of a large number of species (Kirk 1985;Yudin et al 1986). …”
Section: Materials and Methods (A) The Model Systemmentioning
confidence: 99%
“…Volatile cues from pollen have been implicated in pollen selection by host-specific thrips (Kirk, 1985). In bees, Dobson (1987) demonstrated that the solitary bee Colletes fulgidus longiplumosus (Stephen) was attracted to the odour of both the flowers and the pollen of its host plant, and Dobson et al (1999) demonstrated that the presence of pollen or pollen volatiles increased landing responses of bumble bees on flowers.…”
Section: Introductionmentioning
confidence: 99%
“…They also feed on young, tender leaves (Lewis 1973). For many flower thrips, pollen is their major food source (Kirk 1985(Kirk , 2008. This means that the thrips are likely to be able to distinguish their host by its pollen.…”
Section: Introductionmentioning
confidence: 99%